Evaluasi Program Hari Anak Nasional Kota Pontianak dalam Pemenuhan Hak Anak dengan Pendekatan Model CIPP - Risna Nur Shapira; Marini Marini; Munjiat Irvaatun Hidayah; Hurin Ain Fakhirah Alamsyah; Muthia Maslinoviyani (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
National Children's Day (Hari Anak Nasional/HAN) serves as a strategic opportunity to promote public awareness of children's rights in Indonesia. Although Pontianak has been recognized as a Child-Friendly City (Kota Layak Anak/KLA) with the Nindya classification, the implementation of HAN has not been as optimal as that of other cities with similar recognition. This study aims to evaluate the effectiveness of the HAN program in Pontianak using the CIPP (Context, Input, Process, Product) evaluation model. A qualitative descriptive approach was employed. Data were collected through in-depth interviews with members of the Children's Forum and officials from the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning (DP2KBP3A), supported by document analysis of activity reports and budget records. The findings indicate that the HAN program successfully encourages children's active participation in planning and implementing activities while fostering social, leadership, and teamwork skills. The context evaluation revealed strong collaboration between the local government and the Children's Forum. The input evaluation identified adequate resources, although improvements in facilities and facilitator competencies remain necessary. The process evaluation showed effective program implementation, while the product evaluation demonstrated increased public awareness of child protection issues. Nevertheless, the program requires further innovation and better logistical management. These findings are expected to support the improvement of future HAN programs and strengthen Pontianak's efforts to achieve a higher Child-Friendly City classification.